Food, energy, and water the chemistry connection - Ahuja, Satinder 1933- (Amsterdam Elsevier, 2015)
Food, Energy, and Water: The Chemistry Connection examines the inextricable link among the vital resources of food, energy, and water to explain how this relationship should be considered in contemporary research and development. This book will help scientists balance competing concerns of environmental stewardship and innovative, cost-effective product development. Detailed discussions cover how we can utilize these resources without depleting them or decreasing their quality.--Provided by publisher.
1. Overview -- 2. Mass Transport and Chemistry at the Air-Water Interface of Atmospheric Dispersoids -- 3. Water and energy nexus -- 4. Destroying pharmaceuticals in waste water with a minimum use of energy -- 5. Water management for hydraulic fracturing (fracking) -- 6. Water Management in the Area of Thermal in situ Oil Sands: Maximizing Recycle, Minimizing Waste -- 7. Water Scarcity: Global Challenges for Agriculture -- 8. Energy Resource Extraction and Water -- 9. Water availability and quality: Are we at the brink? -- 10. Foundations of water quality monitoring and assessment in United States -- 11. Impact of irrigation water on food -- 12. Edible Materials Defined As Neither Food Nor Drugs -- 13. Biochemical reactors for the removal of metals from mine-impacted water -- 14. Solar Photovoltaic Technologies -- 15. Biofuels -- 16. Water Recovery and Reuse -- 17. Impact of Coal Energy on Water.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Environmental chemistry; Sustainable living; Food contamination; Water quality management; Electronic books